The Legitimate Portion (Legitime Portie) of Legitimate Children in Inheritance Distribution: A Perspective of Legal Justice Theory in Indonesian Civil Law - Puspandari, Rr. Yunita; Indira Swasti Gama Bhakti; Wahyu Prabowo; Hafez, Muhammad; Dwi Anugrahany, Galuh (LPPM Universitas Harapan Bangsa, 2025)
The existence of legitime portie in civil law is determined that the absolute share of a biological child has been determined to be greater than the heirs of groups 2, 3 and 4, if there are adopted children, stepchildren or heirs based on the will, it will be prevented by the existence of legitime portie, but in reality there are cases that occur that are conveyed by advocates, But in reality, there is a case that occurred which was conveyed by an advocate at PBH Peradi related to a biological child who actually did not get an absolute share because the inheritance of both parents was controlled by the stepmother or the father's second wife who was the biological father of the child, this happened because there was no will left before the biological parents died and the property of the father and mother was controlled beforehand by the stepmother or the father's second wife. This research aims to examine how civil law provides protection for the rights of legitimate children as heirs, as well as comparing the implementation of inheritance distribution in the perspective of legal justice theory. The method used is empirical juridical approach with empirical observation through interviews with District Court judges. The results showed that legitime portie is an absolute right protected by law, and any deviation from legal provisions can lead to disputes. The court plays an important role in upholding legal certainty and justice in the distribution of inheritance so that it is necessary to emphasize the importance of applying the principle of justice in the distribution of inheritance to protect the rights of heirs, especially legitimate children, as well as the need for strong legal certainty in the practice of inheritance distribution in society.